Union Contracts and Teacher Professional Development - Paul V. Bredeson (Arizona State University, 2001)
In this article, I report the results of an investigation that examined the impact of teacher union contracts on the development of professional learning communities in schools. There are three primary sources of data used in the study: 1) 100 written teacher union contract documents; 2) structured interview data from 21 educators (school superintendents, principals, directors of staff development, and teacher union representatives; and 3) focus group interview data from educational leaders in schools. The analysis and discussion focus on five areas related to teacher professional development with implications for policy and practice: explicit language covering opportunities for teaching learning in their work; governance and decision making structures, that is, specific provisions covering wages, hours, and conditions of employment; the description of legitimate and sponsored activities for the professional development of teachers; and the resources supporting the on-going professional growth of teachers. The findings indicate that rethinking, restructuring, and organizational re-culturing in schools are initial expressions of a new unionism that has the potential to lead to the development of more powerful professional learning communities in schools.